Acute and multigenerational effects of petroleum- and cellulose-based microfibers on growth and photosynthetic capacity of Lemna minor. (September 2022) - Cui, Rongxue; Kwak, Jin Il; An, Youn-Joo
Abstract: Comparative toxicological assessment studies on the effects of petroleum- and cellulose-based microfibers on aquatic plants are limited. Therefore, we evaluated the acute and 10-generational toxicological effects of two types of petroleum- and cellulose-based microfibers on the duckweed Lemna minor . Plant growth and photosynthesis parameters were monitored as bioindicators. The multigenerational test revealed the following ranking of the microfibers according to the severity of their effects on L. minor : polypropylene > lyocell > viscose > polyethylene terephthalate. The acute tests revealed a significant increase in the energy required to initiate photosynthesis, although the growth of L. minor was not adversely affected by any microfiber. Both petroleum- and cellulose-based microfibers induced adverse effects on the growth and photosynthesis of L. minor in multigenerational tests. The results of the generational tests contribute to the understanding of the long-term adverse effects of microfibers on aquatic plants. Highlights: Toxicity of PP, PET, viscose, and lyocell microfibers on Lemna minor was assessed. Toxicity effects under 3 day acute exposure and 10 generation tests were compared. In acute test, all microfibers adversely affected photosynthesis of L. minor . In mutigenerational test, PP and lyocell inhibited growth and photosynthesis. PET and viscose had negligible effects in multigenerational tests.